A revision of the first Asteropyginae (Trilobita; Devonian) - Bignon, Arnaud Marcel Jacques (2014)
A recent cladistic analysis of the Asteropyginae led to the recognition of the genus Minicryphaeus as one of the most ancestral of this subfamily. A new species, M.giganteus, is described here from the Ihandar Formation (Pragian, Lower Devonian) of Jbel El Mrakib, southern part of the Mader Basin (Morocco). Among other characteristic features, it is almost three times larger than the other species of the genus. The description of this new species provides information on the ancestral character states of the subfamily and necessitated a revision of the oldest known representatives. Moreover, this recent analysis identified Treveropyge as a derived form of asteropygines, whereas it was traditionally considered as ancestral due to one of its oldest species, now Ganetops ebbae nov. comb., which was formerly included in this genus. In order to offer a better view of the ancestral Asteropyginae, the features of M.giganteus nov. sp. and G.ebbae nov. comb. have been coded following the scheme of the previous cladistic analysis. The updated phylogeny reveals that M.giganteus nov. sp. is the sister-group of the other Minicryphaeus species; a paedomorphic event explains their decreasing size. The new phylogeny confirms the basal position of G.ebbae nov. comb. and distinguishes it clearly from the genus Treveropyge, which necessitates the erection of the new genus Ganetops. It appears that the association of G.ebbae nov. comb. with more derived species within the genus Treveropyge disturbed the previous cladistics analysis of the Asteropyginae. Indeed, considering a derived species as root of the subfamily leads necessarily to the formation of two major clades, as it was usually suggested for the Asteropyginae.